Tales From the Chalkface: Using Narratives to Explore Agency, Resilience, and Identity of Gay Teachers - Stones, Samuel; Glazzard, Jonathan (Frontiers in Sociology, 2020)
Existing literature is dominated by accounts which position gay teachers as victims. We were concerned that this only presented a partial insight into the experiences of gay teachers. This study researched the personal and professional experiences of four gay teachers in England. It builds on existing research by presenting positive narratives rather than positioning gay teachers as victims. We use the term “chalkface” to illustrate that all were practicing teachers. The purpose of the study was to explore their experiences as gay teachers throughout their careers. The study used the life history method to create narratives of each participant. Semi-structured interviews were used. The study found that the repeal of Section 28 in England in 2003 did not have an immediate effect on the identities, resilience, and agency of the participants. The 2010 Equality Act in England and changes to the school inspection framework had a greater influence in supporting their agency, resilience, and willingness to merge personal and professional identities. All but one participant managed to use their identities as gay teachers to advance inclusion and social justice through the curriculum. Although the narratives that we have presented do illuminate some negative experiences, the accounts are largely positive, in contrast with existing literature which positions gay teachers as victims.